(3HQfGeL ebJQM dJfejI GdPcGA GdhLOGfj dOi GdCWaGd GdeYhbjf YbdjG GdbGHdjf ddJYdje h CKQg Ydi Sdhcge (B/ s - (3fLdGA eMehO Sdje GHQGgjes; (3YdG YHOGdQMef eMeO (B: s; (3YdGA GdOjf CMeO caGaj (B: s ((3GdbGgQI (B: s (3fLdGA eMehO Sdje GHQGgje (B: s, 2011)
(3gOaJ gPg GdOQGSI Edi EYOGO HQfGeL ebJQM dJfejI GdPcGA GdhLOGfj dOi GdCWaGd GdeYhbjf YbdjG GdbGHdjf ddJYdje h CKQg Ydi Sdhcge(B: (3h cGfJ YjfI GdOQGSI bhGegG (B"(316(B" (3eYhb YbdjG ef eOQSI CMeO Thbj GdacQjI(B: (3GdWad GdeYhb YbdjG jYGfj ef eTcdGJ SdhcjI h GfaYGdjI jLO eYgG UYhHI aj Jcjag eY faSg h eY CaQGO GdeLJeY (B.. (3h EPG de jLO GdQYGjI GdefGSHI hjUHM NWQG Ydi faSg h Ydi GSQJg h GfaYGdjI jLO eYgG UYhHI aj Jcjag eY faSg h Ydi CSQJg h ef Ke CaQGO eLJeYg h jDOj Pdc Edi XghQ GdYOjO ef dGSJLGHGJ GdSdhcjI ZjQ GdeQZhH ajgG h GdJj JJeKd aj Tcd YOhGf Ch aj Tcd YOe JhGab eY GdBNQjf Ch YOe GdbOQI Ydi Jchjf UOGbGJ Ch YdGbGJ Ch aj Tcd GdYRd Ch GfSMGH Yf ef jMjWhf Hgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ h GdHMhK GdJQHhjI (B- (3bSe QjGV GdCWaGd h GdJYdje GdEHJOGFjs
(3UOQ GjVG cbQU eOeLs
Keywords: (3CKQg Ydi Sdhcges; (3GdCWaGd GdeYhbjf YbdjG GdbGHdjf ddJYdjes; (3JfejI GdPcGA GdhLOGfjs